The Influence of Individual Characteristics and Work Environment on Employee Performance at the Simalungun Samsat Office - Kirani, Sapna; Rahmadani, Ika (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
When planning for the present and the future of an organization, human resources are an essential component. Human resources are the engine that propels the agency's operations and the execution of its many tasks. The success of an organization depends on its employees giving their all. This can only be achieved by considering the interplay between the work environment and the encouragement of personal qualities. One of the main aims of this research is to look at how different personality traits and work environments affect productivity. Finding out how these two factors influence productivity through interaction is another important consideration. This study employs a quantitative approach, which involves analyzing populations and samples in accordance with established standards. Research methods, such as quantitative analysis, are employed during data collection to test the hypotheses. The results of this study reveal several important things: first, there is no correlation between an employee's character attributes and their output at the SAMSAT Simalungun Office. Secondly, it has been shown that, in the same setting, the office setting has a substantial and beneficial effect on workers' productivity. Thirdly, we found that both personal qualities and the workplace have a positive and substantial effect on productivity at the SAMSAT Simalungun Office. This finding suggests that agencies should put an emphasis on employee performance by giving more consideration to personal traits. Making an effort to create a more supportive work environment will have a positive impact on employees' overall performance.